Suggesting a simple design method for cold recycled asphalt mixes with asphalt emulsion - Bazrafshan Moghadam, Bahador; Farhad Mollashahi, Hamid (Journal of Civil Engineering and Management, 2017)
Although there are typical and well-known standard methods for designing hot mix asphalt in the world, there is no unique design method for cold recycled asphalt mixes. The current methods are mainly local or even dependent on technology owners due to the diversity of materials and qualitative control limitations. Currently, most of the design methods are based on 4 inch mold. The major problem of these methods is that in the mix design, the effect of aggregates larger than 25 mm is neglected, while this size of aggregates is used in the recycling projects. Therefore, there is a significant difference between in-situ and laboratory mix behaviors. So, 6-inch mold is used. In this study, a simple mix design has been obtained for reclaimed asphalt pavements (RAP) considering the different amount of emulsified asphalt, Portland cement, three gradations, moisture contents, temperatures, and curing times. For this reason, 315 samples were prepared. The results show that the mixes with aggregates larger than 25 mm have a significant difference with 25 mm and smaller aggregates sizes in terms of mechanical properties and moisture susceptibility. Therefore, 6-inch molds should be used for RAP materials that are larger than 25 mm in the mix design.